2022
DOI: 10.1111/jzo.12964
|View full text |Cite
|
Sign up to set email alerts
|

Carnivore coexistence facilitated by spatial and dietary partitioning and fine‐scale behavioural avoidance in a semi‐arid ecosystem

Abstract: Sympatric carnivores compete for similar resources which may lead to dominant species influencing the ecology of subordinate ones. However, carnivores often make use of coevolutionary strategies which enable them to minimise competition with dominant competitors and thus facilitate coexistence. We used camera trapping and scat analysis to investigate the potential competition between leopards (Panthera pardus) and caracals (Caracal caracal) along spatial, temporal and dietary axes to determine the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 93 publications
1
21
1
Order By: Relevance
“…Thirdly, leopard spatial distribution may be influenced by interspecific competition with dominant carnivores [57]. However, as the only remaining large carnivore in the region, these leopards have no direct competitors and are thus not spatially restricted by heterospecifics [61].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, leopard spatial distribution may be influenced by interspecific competition with dominant carnivores [57]. However, as the only remaining large carnivore in the region, these leopards have no direct competitors and are thus not spatially restricted by heterospecifics [61].…”
Section: Discussionmentioning
confidence: 99%
“…The primary (main) prey base for leopards across the Western Cape include common duiker (duiker; Sylvicapra grimmia , Linnaeus, 1758), Cape grysbok (grysbok; Raphicerus melanotis , Thunberg, 1811), klipspringer ( Oreotragus oreotragus , Zimmermann, 1783), and grey rhebok (rhebok; Pelea capreolus , Forster, 1790), as well as rock hyrax (hyrax; Procavia capensis , Pallas, 1766), Cape porcupine (porcupine; Hystrix africaeaustralis , Peters, 1852), and chacma baboons (baboon; Papio ursinus , Kerr, 1792) ( Martins et al, 2010 ; Drouilly, Nattrass & O’Riain, 2018 ; Mann et al, 2019 ; Müller et al, 2022a ). In addition to suffering retaliatory killings, these species are also targeted for the illegal harvesting of bushmeat by means of snaring in the province ( Nieman et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Theory on top-down ecosystem regulation and suppressive effects of large carnivores indicates that body size has a strong influence on the intensity of competitive effects (Palomares and Caro 1999;Donadio and Buskirk 2006). As such, it would be expected that the presence of leopard has a greater effect on caracal site use, as the two species are closer in body size and share a higher degree of dietary overlap (Müller et al 2022). However, recent studies have indicated that the network of intraguild competition and top-down mediated effects are more extensive than previously thought (Prugh and Sivy 2020;Curveira-Santos et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of caracal spatiotemporal responses to leopard presence is surprising, as the two species can display high dietary overlap (Müller et al 2022) and leopard are known to kill caracal when encountered (Curveira-Santos et al 2022). Given the potential for dietary overlap (Caro and Stoner 2003;Müller et al 2022), caracal and leopard may be selecting similar habitat characteristics for preferred prey, and this could explain the positive relationship between caracal site use and leopard abundance. Previous studies have indicated that whilst caracal and leopard potentially compete for prey, they can exhibit a high level of spatial and temporal overlap and facilitate coexistence using fine-scale avoidance strategies (Müller et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation